2006
DOI: 10.3892/or.16.6.1343
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of Hochu-ekki-to on endometrial carcinogenesis induced by N-methyl-N-nitrosourea and 17β-estradiol in mice

Abstract: An evaluation of the effects of a traditional Chinese herbal medicine, Hochu-ekki-to (Bu-zong-yi-qi-tang) on endometrial carcinogenesis was performed in experiments with female mice. In the short-term experiment, dietary exposure of Hochu-ekki-to (0.2% for 2 weeks) decreased the estradiol-17ß (E2)-stimulated expression levels of c-jun (P<0.001), tumor necrosis factor (TNF)-• (P<0.005), estrogen receptors (ER)-• (P<0.001) and ER-ß (P<0.005), as determined by reverse transcription-polymerase chain reaction and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 20 publications
(29 reference statements)
0
23
1
Order By: Relevance
“…We have obtained evidence that persistent cholangitis after bilioenterostomy in hamsters accelerates the development of biliary carcinoma through an increase in the proliferative activity of the biliary epithelium in accordance with the severity of cholangitis (9,10) and that etodolac, a selective COX-2 inhibitor, reduces both the occurrence of severe cholangitis and the acceleration of biliary epithelial cell kinetics after bilioenterostomy in hamsters, resulting in the prevention of BOP-induced biliary carcinogenesis (34). Recently, some studies have proved that TJ-41 reduced the development of several kinds of cancer (17)(18)(19)(20) and activities of inflammatory cytokines (35)(36)(37). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have obtained evidence that persistent cholangitis after bilioenterostomy in hamsters accelerates the development of biliary carcinoma through an increase in the proliferative activity of the biliary epithelium in accordance with the severity of cholangitis (9,10) and that etodolac, a selective COX-2 inhibitor, reduces both the occurrence of severe cholangitis and the acceleration of biliary epithelial cell kinetics after bilioenterostomy in hamsters, resulting in the prevention of BOP-induced biliary carcinogenesis (34). Recently, some studies have proved that TJ-41 reduced the development of several kinds of cancer (17)(18)(19)(20) and activities of inflammatory cytokines (35)(36)(37). …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, TJ-41 has recently been reported to activate macrophages and natural killer (NK) cells (13)(14)(15). Moreover, some studies have demonstrated that TJ-41 inhibits experimental liver metastasis (16) and also exerts an anti-neoplastic effect in several kinds of malignant tumors, including skin cancer, hepatoma, ovarian cancer, and uterine cancer (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…These data support that BJIKT augmented antitumor immune response in stress-burdened, tumor-bearing mice 23 . Onogi's group performed endometrial carcinogenesis, in ICR mice, induced by N-Methyl-N-Nitrosourea (MNU) into the left uterine tube and normal saline was injected into the opposite side 24 . Diet with 17ß-estradiol (E2) alone, E2 plus BJIKT, was given and incidence of prenoplastic and neoplastic mouse endometrial lesions were measured 24 .…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Onogi's group performed endometrial carcinogenesis, in ICR mice, induced by N-Methyl-N-Nitrosourea (MNU) into the left uterine tube and normal saline was injected into the opposite side 24 . Diet with 17ß-estradiol (E2) alone, E2 plus BJIKT, was given and incidence of prenoplastic and neoplastic mouse endometrial lesions were measured 24 . The incidence of adenocarcinoma was significantly less in BJIKT treated mice 24 .…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation